Higher Order Thinking Skill (HOTS) Analysis of Students of the Institute of Islamic and Arabic Sciences (LIPIA) on Rewriting Ta'bir Books in Book Creator - Madian M. Muchlis; Taufik Hidayat; Ili Yanti (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2023)
Higher Order Thinking Skill (HOTS ا) is a higher order thinking skill that is not only able to remember, understand and explain, but is able to analyze, evaluate and create a problem. HOTS can not only be seen from the work of the questions but can also be seen from the side of creative ability in Arabic material. Rewriting the book